Efficient q-integer linear decomposition of multivariate polynomials. (November 2021) - Giesbrecht, Mark; Huang, Hui; Labahn, George; Zima, Eugene
Abstract: We present two new algorithms for the computation of the q -integer linear decomposition of a multivariate polynomial. Such a decomposition is essential for the treatment of q -hypergeometric symbolic summation via creative telescoping and for describing the q -counterpart of Ore-Sato theory. Both of our algorithms require only basic integer and polynomial arithmetic and work for any unique factorization domain containing the ring of integers. Complete complexity analyses are conducted for both our algorithms and two previous algorithms in the case of multivariate integer polynomials, showing that our algorithms have better theoretical performances. A Maple implementation is also included which suggests that our algorithms are much faster in practice than previous algorithms.